¿Cómo financiar el acceso abierto en ciencias humanas y sociales? Una propuesta bienintencionada - Abadal, Ernest (Anuario ThinkEPI, 2015)
Reseña del informe: Kenniso, Rebecca;Â Norberg, Lisa (2014). A scalable and sustainable approach to open access publishing and archiving for humanities and social sciences. KN Consultants. http://knconsultants.org/toward-a-sustainableapproach-to-open-access-publishing-and-archiving